2010
DOI: 10.1016/j.ejvs.2010.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Elastic Components of the Venous Wall on the Biomechanical Properties of Different Veins Used for Arterial Reconstruction

Abstract: The histological structure directly influences the biomechanical properties of venous wall with rSV showing least compliance and cSV the greatest compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…Non-linear and viscoelastic behaviour is observed with veins and, adding to venous structural complexity, the microstructure and mechanical properties of veins vary with their anatomical location, position in the vascular hierarchy and stress state (Rossmann, 2010). The composition of various elastic components such as elastin and collagen influence the biomechanical characteristics of veins (Krasi nski et al 2010). The amount of collagen I and IV present in the walls of veins differs between competent and incompetent vessels, with competent human saphenous veins showing a larger amount of collagen IV, and incompetent veins displaying a greater amount of collagen I and elastin leading to a greater stiffness (Krasi nski et al 2010).…”
Section: Three-dimensional Printing Of Skinmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-linear and viscoelastic behaviour is observed with veins and, adding to venous structural complexity, the microstructure and mechanical properties of veins vary with their anatomical location, position in the vascular hierarchy and stress state (Rossmann, 2010). The composition of various elastic components such as elastin and collagen influence the biomechanical characteristics of veins (Krasi nski et al 2010). The amount of collagen I and IV present in the walls of veins differs between competent and incompetent vessels, with competent human saphenous veins showing a larger amount of collagen IV, and incompetent veins displaying a greater amount of collagen I and elastin leading to a greater stiffness (Krasi nski et al 2010).…”
Section: Three-dimensional Printing Of Skinmentioning
confidence: 99%
“…The composition of various elastic components such as elastin and collagen influence the biomechanical characteristics of veins (Krasi nski et al 2010). The amount of collagen I and IV present in the walls of veins differs between competent and incompetent vessels, with competent human saphenous veins showing a larger amount of collagen IV, and incompetent veins displaying a greater amount of collagen I and elastin leading to a greater stiffness (Krasi nski et al 2010). The challenges in replicating veins would be similar to that of arteries given their similar structure.…”
Section: Three-dimensional Printing Of Skinmentioning
confidence: 99%
See 1 more Smart Citation
“…The contents of collagen I, III and IV and elastin in the human femoral vein (FV), incompetent saphenous vein (ISV) and competent saphenous vein (CSV) were measured by using computer-image-analysis system connected to a microscope based on immunohistochemically staining technique in terms of area fraction occupied by collagen or elastin in transverse sections [29].…”
Section: Histology Of Venous Wallmentioning
confidence: 99%
“…The SFV is now well established as an autologous graft in reconstructive arterial and venous vascular surgery. Histomorphological investigations have shown that the collagen and elastin composition of the vein wall and its associated compliance is comparatively similar to that of an autologous artery, thereby also explaining the low tendency toward marked myointimal hyperplasia [ 8 ]. In addition to the excellent data on fully autologous reconstruction in septic vascular surgery involving the repair of infected conventional vascular grafts or mycotic aneurysms [ 6 , 7 , 9 16 ], results on the successful use of this approach in infected stents or stent grafts are also available [ 17 19 ].…”
Section: Indications For Use Of the Superficial Femoral Veinmentioning
confidence: 99%